Roots of drought stress: 40 year of research in a Scientometrics analysis - Ana Carolina Roque Cardoso; Pedro Gomes Peixoto; Heytor Lemos Martins; David Luciano Rosalen (Discover Agriculture)
Abstract Drought poses a significant challenge to agriculture and ecosystem sustainability, with critical repercussions on agricultural production. This study addresses gaps in the understanding of plants' genetic and physiological responses to water stress. Our scientometric analysis of research trends over the past 40 years reveals a substantial increase in published studies since the 2000s, indicating an increasing emphasis on innovative strategies to increase plant resilience to drought. The main findings reveal new genetic and physiological markers related to drought tolerance and an increased focus on integrated management practices that combine genetic improvement with efficient water use. This research provides an in-depth view of research trends aimed at mitigating the adverse effects of water stress on crops.